2014
DOI: 10.1534/g3.113.008870
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern and Distribution of Deleterious Mutations in Maize

Abstract: Most nonsynonymous mutations are thought to be deleterious because of their effect on protein sequence and are expected to be removed or kept at low frequency by the action of natural selection. Nonetheless, the effect of positive selection on linked sites or drift in small or inbred populations may also impact the evolution of deleterious alleles. Despite their potential to affect complex trait phenotypes, deleterious alleles are difficult to study precisely because they are often at low frequency. Here, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 68 publications
14
69
1
Order By: Relevance
“…The enrichment of deleterious alleles in low-recombination regions is expected because reduced recombination permits deleterious alleles to hitchhike to high frequency during selective sweeps (21). However, our finding contrasts with a recent study of putatively deleterious nonsynonymous polymorphisms in maize, which were not significantly enriched in regions of low recombination (36). We believe our methods are better able to assess whether an increase in the frequency of deleterious alleles accompanies reduced recombination due to our use of a measure that does not rely on genome annotation.…”
Section: Discussioncontrasting
confidence: 99%
“…The enrichment of deleterious alleles in low-recombination regions is expected because reduced recombination permits deleterious alleles to hitchhike to high frequency during selective sweeps (21). However, our finding contrasts with a recent study of putatively deleterious nonsynonymous polymorphisms in maize, which were not significantly enriched in regions of low recombination (36). We believe our methods are better able to assess whether an increase in the frequency of deleterious alleles accompanies reduced recombination due to our use of a measure that does not rely on genome annotation.…”
Section: Discussioncontrasting
confidence: 99%
“…This negative correlation holds using allele frequency derived from our 12 parental lines (S4 Fig), though as expected is less significant given the smaller sample size. SNPs found in regions of the genome with low recombination also show higher overall GERP scores (Fig 1d), a trend particularly noticeable around centromeres (S5 Fig). These results match previous empirical findings in maize that deleterious alleles are rare [19] and most abundant in the lowest recombination regions [17,40,53], and support the use of GERP scores as a quantitative measure of the long-term fitness effects of an observed variant.…”
Section: Annotation Of Deleterious Allelessupporting
confidence: 88%
“…For binary traits, such as those frequently used in human disease case-control studies, more complex genetic models, including dominance and overdominance, can be explicitly tested (39,40). Although this is rarely done in the analysis of continuous traits, a few studies have reported associations of heterotic traits with heterozygosity (41)(42)(43)(44)(45). We selected two linear mixed models to search for associations between genotype and phenotype using FaSTLMM software in the easyGWAS framework (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…If heterosis is the reverse of inbreeding depression, then the degree of heterosis should positively correlate with the genetic distance between parents, and causal alleles should be rare with small phenotypic effects (8,(51)(52)(53)73). Several dominantly acting loci have been shown to contribute to heterosis (29,77,78), and more recently, heterosis-associated loci in maize have been shown to be enriched for deleterious mutations (43). Although dominance remains the prevailing explanation, some assumptions of this hypothesis are not consistently supported; the correlation between the degree of heterosis and the genetic distance between parents is not always evident (37,(55)(56)(57)(79)(80)(81)(82), and there are loci with moderate effect sizes (29,77,78).…”
Section: Arabidopsis Thaliana In the Context Of Traditional Heterosismentioning
confidence: 99%